PERAN KOMISI INFORMASI PROVINSI JAWA TENGAH DALAM MENDORONG TERCAPAINYA KETERBUKAAN INFORMASI PUBLIK DI JAWA TENGAH - Aditya Satrio DW; Priyatno Harsasto .; Neny Marlina . (Journal of Politic and Government Studies, 2017)
ABSTRACTStudy of the role of Central Java Information Commissions in encouragingdisclosure of information in Central Java, has purpose to explain the role ofCentral Java Information Commission in encouraging disclosure of informastionas on UU KIP and Additionally described obstacle and proponent factors KI rolein encouraging the achievement of a disclosure in central Java province.In the implementation of the study authors using agency theory, agencytheory which describes the relationship between the donor authority / principal(KI Prov Central Java) to those who run errands / agent (public board) bound bythe Nexus of Contract. This study used qualitative methods, with data collectiontechniques such as interviews as the primary data and documents as secondarydata. In determining the informants using purposive sampling technique, in whichmembers of KI Central Java Province as an informant.In carrying out its role KI Prov Central Java continue to emphasize to thepublic board that is to have a professional Official Information andDocumentation (PPID), where PPID is the people who are assigned specifically tobe PPID instead of an employee that already exist given the dual position intoPPID, found also the group that uses the public information for his own benefit sothat people can not get the necessary information, and also the elements PPIDconducting information asymmetry, where PPID is not doing a deal that is setexample is PPID non-reporting services annual information and does not provideinformation on people for no apparent reason.Finally, although in encouraging disclosure of information in Central JavaKI got a lot of obstacles, but KI continues to strive as much as possible, one ofthem by utilizing the existing civil society so that they continue to force publicbodies to be more transparent. As well as the support of the Governor of CentralJava in the form of operational funds and Governor Regulation on publicinformation services that make public bodies more transparent to the public.Keywords: Disclosure informastion, Asymmetric Information, Komisi Informasi